Defect-Induced Tunable Permittivity of Epsilon-Near-Zero in Indium Tin Oxide Thin Films - Jiqing Lian; Dawei Zhang; Ruijin Hong; Peizhen Qiu; Taiguo Lv; Daohua Zhang (Nanomaterials, 2018)
Defect-induced tunable permittivity of Epsilon-Near-Zero (ENZ) in indium tin oxide (ITO) thin films via annealing at different temperatures with mixed gases (98% Ar, 2% O2) was reported. Red-shift of λENZ (Epsilon-Near-Zero wavelength) from 1422 nm to 1995 nm in wavelength was observed. The modulation of permittivity is dominated by the transformation of plasma oscillation frequency and carrier concentration depending on Drude model, which was produced by the formation of structural defects and the reduction of oxygen vacancy defects during annealing. The evolution of defects can be inferred by means of X-ray diffraction (XRD), atomic force microscopy (AFM), and Raman spectroscopy. The optical bandgaps (Eg) were investigated to explain the existence of defect states. And the formation of structure defects and the electric field enhancement were further verified by finite-difference time domain (FDTD) simulation.